2016
DOI: 10.1302/2046-3758.55.2000596
|View full text |Cite
|
Sign up to set email alerts
|

A review of current surgical practice in the operative treatment of proximal humeral fractures

Abstract: ObjectivesThe PROximal Fracture of the Humerus: Evaluation by Randomisation (PROFHER) trial has recently demonstrated that surgery is non-superior to non-operative treatment in the management of displaced proximal humeral fractures. The objective of this study was to assess current surgical practice in the context of the PROFHER trial in terms of patient demographics, injury characteristics and the nature of the surgical treatment.MethodsA total of ten consecutive patients undergoing surgery for the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…As for the proximal femur, osteoporosis importantly affects the outcome of fixation. In recent years, in front of alarming percentage of complications as humeral head articular surface perforation by screws with percentage up to 73 % of cases [6], authors from different countries of the world focused their attention on conservative treatment also for complex displaced fractures [24][25][26].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…As for the proximal femur, osteoporosis importantly affects the outcome of fixation. In recent years, in front of alarming percentage of complications as humeral head articular surface perforation by screws with percentage up to 73 % of cases [6], authors from different countries of the world focused their attention on conservative treatment also for complex displaced fractures [24][25][26].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This survey is one of various approaches to measuring impact of trials such as PROFHER. An intended repeat of the study by Dean et al 11 that reviewed surgical practice in 11 United Kingdom hospitals between January 2014 and March 2015, thus before the Journal of the American Medical Association publication of PROFHER, 1 will be valuable. However, as illustrated for the Distal Radius Acute Fracture Fixation Trial, using the date of main publication as the threshold for detecting change may be misleading.…”
Section: Discussionmentioning
confidence: 99%
“…28 Fixed angle anatomic locking plates have become the most commonly utilised implants for fixation of proximal humerus fractures. 20,31 The mode of failure of locked plates differs from conventional plates which will fail by the loosening of individual screws sequentially whereas locked plates will fail by simultaneous cut-out of multiple screws or by fracture of the bone at the stress riser at the end of the plate. 32 It has been shown that good restoration of support to the inferomedial calcar is important in maintaining fracture reduction.…”
Section: Platesmentioning
confidence: 99%
“…With the large variation in fracture types in this study there might well be subgroups that do clearly benefit from surgery, but these remain unidentified. 66…”
Section: Conservative Treatmentmentioning
confidence: 99%